The effect of a herbal formulation on the incidence and severity of upper respiratory symptoms in healthy volunteers : an open-label, randomized controlled clinical trial - Goonaratna, C.; Sooriyarachchi, M.R. (Medical Council of Sri Lanka, 2012)
Introduction Many traditional preparations with varying combinations of herbs have been used for over 1500 years to treat upper respiratory ailments, and reduce their incidence and severity. Link Samahan® is a formulation containing the extract of 14 such medicinal plants. Objectives To test the efficacy of Link Samahan® in reducing the incidence and severity of upper respiratory symptoms in consenting healthy volunteers. Setting MAS Linea Aqua, a factory with over 3000 employees, having its own health care centre with a qualified matron and visiting medical officers. Methods 956 healthy volunteers took daily either one sachet of Link Samahan® in hot water (test group, n=465, mean age 29.5 ± 7.7 years, women 418) or only plain tea (control group n=491, mean age 29.7 ± 7.9, women 448), for 84 consecutive days, and recorded the incidence and severity of 15 upper respiratory symptoms daily in a purpose-designed form. Results At the end of 84 days, when compared to the control group, the average incidence of symptoms in the test group showed highly significant reductions at p<0.001 for 6 symptoms and at p<0.005 for 3 symptoms, and at p<0.05 for the remaining 6. Reduction of average incidence over time also was highly significant (p<0.001) for 2 symptoms and (p<0.005) for 7, and significant (p<0.05) for 4 symptoms, but only marginal for the balance 2. Severity was significantly reduced (p<0.05) for 7 symptoms, and reduced also for the other 8 according to descriptive analysis, though not significant at the 5% level. Conclusions The results indicate that Link Samahan® taken as one sachet daily significantly reduces average incidence, incidence over time, and severity of 15 upper respiratory symptoms in healthy adults
Keywords: upper respiratory symptoms, short form WURSS-21, herbal medicinal product